Clinical and histopathological characteristics, diagnosis and treatment, and comorbidities of Bowen’s disease: a retrospective study - Zhou, Cheng; Jiang, Bin; Zhang, Kaoyuan; Wu, Jingwen; Huang, Cong; Xu, Ning; Ye, Tinglu; Chen, Bancheng; Yu, Bo; Zou, Yanfen; Shen, Changbing (Frontiers in Medicine, 2023)
Background Bowen's disease (BD) is a slow-growing precancerous skin condition, often concurrent with other diseases, with a high misdiagnosis rate. Previous studies show that patients with BD in different populations have differentiated characteristics.Materials and methods A retrospective study was conducted in a tertiary hospital in Shenzhen,China. Data about demographic information, diagnosis and treatment, clinical and pathological characteristics, and comorbidities of 50 patients with BD were collected and analyzed.Clinical data of onset age and disease course of 43 patients with BD were available, the average onset age of male and female patients are 55.1 (standard deviation (SD) = 15.29) and 58.2 (SD = 15.59) years old, respectively; the average disease course of male and female patients are 25.3 (SD = 28.63) and 33.9 (SD = 49.65) months, respectively. The onset age (P = 0.52) and disease course (P = 0.49) between males and females are not significantly different.Interestingly, there is a negative correlation between onset age and disease course (r = -0.245, P = 0.11). The clinical diagnosis rate of BD was relatively low, BD was misdiagnosed as Bowenoid papulosis (10.00%), actinic keratosis (8.00%), basal-cell carcinoma keratosis (8.00%), seborrheic keratosis (6.00%), and pigmented naevus (4.00%). Trunk and limbs were the most common distribution sites of BD lesions, and 94.00% patients with BD were treated with surgical resection. There are 66.00% patients with BD had comorbidities, including skin diseases (48.48%), cardiovascular diseases (39.39%), gastrointestinal disease (30.30%), respiratory diseases (27.27%), and tumors (18.18%). The most commonly observed histopathological characteristics of BD were squamous cell hyperplasia (86.00%), hyperkeratosis with hypokeratosis (48.00%), disordered maturation with atypical keratinocytes (74.00%), atypical mitoses (60.00%), dermal inflammatory cell infiltration (36.00%), and koilocytosis (22.00%).Conclusion BD often occurs in the middle-aged and elderly people, and is easily misdiagnosed.The onset age and disease course of BD are not significantly different between males and females, whereas there is a negative correlation between the onset age and disease course. BD is more likely to occur in the trunk and limbs in Chinese population, and most patients with BD are diagnosed with comorbidities.